The seed pod : facilitating self organizing robust settlement patterns in developing countries - Auerbach, Rupert (School of Architecture, Planning and Geomatics, 2016)
Darwin's theory of natural selection defines a conscious process of self organisation in which traits become more or less common in such a way that an organism is able to survive and flourish in a particular environment. Rapid growth in the last fifty years made possible by more and more efficient ways of harvesting resource has created rapid environmental change. Intricately balanced ecologies that have taken millions of years to evolve are suffering from unravelling diversity. It is essential that ballooning populations around the world develop systems in which individual settlements positively affect surrounding ecologies. The effect of sick ecologies and drained resources are most harshly felt by the poor in developing countries. The situation boils down to provision of an element which firstly provides the vital requirements for survival while positively affecting the ecologies of which it is a part; secondly allows settlements to adapt over time according to the traits of users in an environment rather than those of a hierarchical disconnected third party and thirdly insures that survival does not depend on having lots of children. The seed pod aims to grow a localized ecology which allows urbanisation for the poor in developing countries to follow self organizing settlement patterns. Goals: Healthy living becomes possible in the local ecology without employment (unemployment is a reality) Financial resources are freed up for facilities such as schools Social support networks strengthen Minimization of strain on resources allows diversity to flourish Construction of instant communities is replaced by a robust self organizing process of development with the capacity to adapt to rapidly changing conditions The seeds are sown and the settlement grows organically from each unique social and ecological environment Empowerment, self reliance and local skills are generated A community lease and a community-managed register of rights holders with the potential for upgrade to individual ownership provides people the opportunity for long term investment in a great living environment. Resolution at a micro scale is likely to result in more conflict then provision of large scale identically defined units. If systems are put in place to help resolve conflict, however, the process would be tangibly more democratic. The seed pod goes hand in hand with a system for conflict resolution illustrated by the phased growth of Green Park an informal settlement in Driftsands Nature Reserve and by notionally suggesting the integration of the education system into the community through a transition of safe, contained learning spaces and permeable public spaces.